Competence Certification Information System Asn at West Java Bpsdm LSP - Ayi Ratna Kristiani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
ASN Competency Certification is the process of determining and recognizing the achievement of ASN Employee Competence which is carried out systematically and objectively through competency tests/verification in accordance with competency standards that refer to the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 11 of 2018 concerning Competency-Based Apparatus Human Resources Development System in Environment Ministry of Home Affairs and Local Government. ASN Competency Certificate is written evidence of acknowledgment of mastery of ASN Competencies at certain levels/types of positions in accordance with the standards set by BKN. The series of procedures for processing competency certification test data are currently not systemized properly and are still carried out manually starting from the registration stage to storing test results. The LSP data management method which is currently still done manually needs to be changed to a more systematic and automatic method. Therefore, to define the required ASN data according to the needs and to streamline data exchange between the system and the interface, it will be made using an API-based ASN Competency Certification Test System with GraphQL architecture.